The effect of intellectual capital on sustainable competitive performance: field research in a sample of private colleges (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:                  This research seeks to test the influence of intellectual capital as an explanatory variable and its components (human capital, structural capital, relational capital) and sustainable competitive performance as a responsive variable and its components (reducing service delivery cycle time, rapid response to market demand, increasing customer satisfaction, providing better Quality of service, increasing market share)” through a field study, and here the research problem was diagnosed in an attempt to answer the following question: Is there awareness among the senior management within the private colleges (researched) of the importance of employing intellectual capital in sustainable competitive performance? "Because of the importance of the private education sector, the research community, which was established more than 20 years ago, was chosen to obtain sustainable competitive performance, and it was conducted in six private colleges located in Baghdad, namely (Al-Turath University College, Al-Mansour University College, Al-Rafidain University College, Al-Mamoun University College, and Baghdad University for Economic Sciences, Baghdad College of Medical Sciences (formerly Baghdad Pharmacy), and the research sample consists of (87) individuals from the deans of colleges and their assistants as well as the heads of scientific and administrative departments. The researcher adopted the descriptive analytical approach, and the questionnaire was used as the main tool for collecting private data. On the field side, the data was then analyzed and hypotheses were tested using appropriate statistical tools, and then the data obtained was processed with a number of statistical tools and methods, which were divided into the following groups: Confirmatory factor analysis: - (arithmetic mean, standard deviation, coefficient of variation, linear regression Simple, multiple regression........) and a set of ready-made programs was used, namely (SPSS and (AMOS). The results showed that there is an impact of intellectual capital and its dimensions on competitive performance and its dimensions.